2021
DOI: 10.1016/j.acra.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Online Liver Imaging Course; Pivoting to Transform Radiology Education During the SARS-CoV-2 Pandemic

Abstract: Purpose: The SARS-CoV-2 pandemic has drastically disrupted radiology in-person education. The purpose of this study was to assess the implementation of a virtual teaching method using available technology and its role in the continuity of education of practicing radiologists and trainees during the pandemic. Methods: The authors created the Online Liver Imaging Course (OLIC) that comprised 28 online comprehensive lectures delivered in realtime and on-demand over six weeks. Radiologists and radiology trainees w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
1
15
0
2
Order By: Relevance
“…In comparing pre-test and post-test results, the cohort of students performed better on the post-test after completing the virtual rotation, with statistically significant results. In the same fashion, several studies showed the effectiveness of virtual teaching of radiology [ 2 , 13 ]. In a study from Harvard Medical School, 111 medical students enrolled in a virtual radiology curriculum and were given a final exam at the conclusion of the rotation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In comparing pre-test and post-test results, the cohort of students performed better on the post-test after completing the virtual rotation, with statistically significant results. In the same fashion, several studies showed the effectiveness of virtual teaching of radiology [ 2 , 13 ]. In a study from Harvard Medical School, 111 medical students enrolled in a virtual radiology curriculum and were given a final exam at the conclusion of the rotation.…”
Section: Discussionmentioning
confidence: 94%
“…The final exam results were compared to those of the final exam taken when the rotation was in-person in prior years, with the final exam scores being similar to those of the in-person rotation. This demonstrates the quality of online education delivery with minimal to no deficiency when compared to in-person learning [ 13 ]. In the Egyptian cohort that we assessed, employing a similar comparison model with the performance of students enrolled in an in-person radiology curriculum at Egyptian medical schools pre-COVID-19 pandemic could be useful to assess efficacy for future implementation of online learning.…”
Section: Discussionmentioning
confidence: 99%
“…Auch wenn es sich bei dieser Arbeit nur um die Evaluation eines Kurses handelt, zeigen die Daten, dass onlinebasierte Lehrkonzepte in der Radiologie vielfältig anwendbar sind, und es sich dabei, vergleichbar zu Studien aus Amerika und Großbritannien [2][3][4][5][6]11], um ein zukunftsträchtiges Konzept handelt. Daher sollte man an der weiteren Optimierung der Onlinelehre arbeiten.…”
Section: Ausblickunclassified
“…A post-course survey was sent to all registrants with 487 respondents to the survey. The results of the survey were published [1] and highlights from the survey include: a. On average, there were 89 live participants per session and 750 YouTube views per recording b.…”
Section: Looking Backmentioning
confidence: 99%